CLINICAL EFFECTIVENESS OF OSMOTIC LAXATIVE DRUGS IN EARLY POSTOPERATIVE PERIOD IN CHILDREN WITH CHRONIC COLON STASIS - P.V. Ivanov; I.V. Kirgizov; I.A. Shishkin; K.N. Baranov; A.A. Mikhailovskiy ("Paediatrician" Publishers LLC, 2010)
The clinical effectiveness of osmotic laxative drugs based on lactulose in restoration of gastrointestinal tract function in early postoperative period after transanal interventions and laparoscopic operations in 53 children 2-17 years old was studied. All patients had non-functional (cologenic and proctogenic) constipation. Patients underwent full-thickness laparoscopic or transanal biopsy due to suspicion of gastrointestinal malformation presence. Children from base group (n = 28) used lactulose (Duphalac) from the second day of postoperative period (dose complied with the age) once daily, in the morning. The control group (n = 25) received subcutaneous or intramuscular proserinum for the stimulation of peristalsis. Blood tests with serum potassium control were performed on 2nd and 4th day. The study showed clinical effectiveness of lactulose in treatment of postoperational hypotonic constipation in children with colon malformations.  Key words: children, gastrointestinal malformations, postoperative period, chronic constipation, lactulose. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):122-125)